Impact of nutritional guidance on various clinical parameters in patients with moderate obesity: A retrospective study - Oda, Kayoko; Anno, Takatoshi; Ogawa, Nozomi; Kimura, Yukiko; Kawasaki, Fumiko; Kaku, Kohei; Kaneto, Hideaki; Takemasa, Mutsuko; Sasano, Miyori (Frontiers in Nutrition, 2023)
Context: The aim of this study is to examine whether nutritional guidance with registered dietitian interventions is appropriately provided especially for moderate obese patients, since it may be more effective in Japanese patients. Methods: Since there is a system of nutritional guidance with registered dietitian to subjects with over 30 kg/m2 of body mass index (BMI) in Japan, we recruited 636 subjects with obesity who were over 30 kg/m2 of BMI in Kawasaki Medical School General Medical Center from April, 2018 to March, 2020 with review medical records. Second, we recruited 153 subjects who underwent blood examination before nutritional guidance and after at least once 3-6 months later, to evaluate whether nutritional guidance continued follow-up intervention for obese patients and were effective. We evaluated the difference of BMI and metabolic markers between subjects with and without receiving nutritional guidance with registered dietitian. Results: 636 subjects with obesity who were over 30 kg/m2 of BMI were included in this study. 164 subjects with obesity received nutritional guidance with registered dietitian at least once, but 472 subjects did not receive. Most of nutritional guidance with registered dietitian were ordered from internal medicine (81.1 %). On the other hand, internal medicine was also the most common department which did not perform them; however less than half (49.2 %) received them. In second analysis, we compared the obese subjects, who underwent blood examination, with receiving nutritional guidance with registered dietitian (n=70) and without receiving them (n=54). Body weight and BMI in subjects with and without receiving nutritional guidance with registered dietitian were not significant, respectively. Dyslipidemia-associated metabolic markers were significantly decreased after receiving nutritional guidance compared to those without receiving them (total cholesterol, -9.7 ± 29.3 vs. 2.3 ± 22.0 mg/dL (p= 0.0208); low-density lipoprotein cholesterol, -10.4 ± 30.5 vs. -2.0 ± 51.0 mg/dL (p= 0.0147), respectively). Other metabolic markers also tended to decrease, although it did not reach a statistical significance. Conclusion: It is rare for subjects with only obesity to receive nutritional guidance. However, once nutritional guidance with registered dietitian is provided, improvement in BMI and metabolic parameters can be expected.